Case report: Successful treatment of chorioptic mange in two Belgian draft horse foals with topical ivermectin - Brys, Marieke; Den Hondt, Stien; Saey, Veronique; Claerebout, Edwin; Chiers, Koen (Frontiers in Veterinary Science, 2024)
IntroductionVarious draft horse breeds, especially breeds with abundant feathering on the lower limbs, are known to be susceptible to chorioptic mange. Clinical signs of chorioptic mange encompass intense pruritus leading to self-mutilation and hair loss, thickening of the epidermis, and the formation of hyperkeratotic crusts and scabs. Despite the frequent occurrence and high impact of this condition, treatment options are limited, with a conspicuous absence of registered products formulated for equines, and especially foals. This limited availability of approved products highlights the necessity for alternative approaches to effectively address chorioptic mange in draft horse populations, given the severity of the clinical signs and their negative impact on the well-being of infested horses.MethodsTwo 9-months old Belgian draft horse foals with clinical signs of severe pruritus and skin scaling on the distal legs were included. Both horses tested positive for living mites by means of superficial skin scrapings. Topical treatment with ivermectin at a dose of 1 mg/kg body weight was applied twice with 1 week interval, directly onto the distal legs of the horses.ResultsIn both cases, the mites were morphologically identified as Chorioptes bovis. Negative scrapings were obtained 7 days after the second treatment. Pruritus resolved in both horses within 2 days after the first treatment. Clinical signs consisting of skin scaling and crusting in the pastern region had resolved as well at 1 week and 3 weeks after the second treatment, respectively.ConclusionThis case report presents the first successful treatment of two clinical cases of chorioptic mange in Belgian draft horse foals with 1 mg/kg topical ivermectin, applied directly onto the distal legs.